Study on the process of Adopting Women's Judo as an Olympic Sport (1975-1985). Pros and Cons inside the IOC and the IJF - Yamazaki, Yuta (Πανεπιστήμιο Πελοποννήσου, 2024)
This study is based on the meeting minutes of the International Olympic Committee (IOC) General Assembly and Executive Board (EB), aiming to elucidate the process of adopting women's judo as an Olympic sport and reveal the negotiations that took place between the IOC and International Judo Federation (IJF). Previous studies indicated that the IJF initiated negotiations with the IOC for the inclusion of women's judo in the Olympic program starting in 1979. However, this study reveals that lobbying efforts for the adoption of women's judo as an Olympic sport were underway as early as 1975. This was the work of then IJF President Charles Palmer, a British-born president. It was suggested that the delay in adopting women's judo as an Olympic sport may have resulted from the existence of opposing and supporting factions within the IOC regarding the adoption of women's judo. The minutes of the meeting included a discussion of the global popularity of women's judo and whether women's judo should be considered a new sport or an extension of men's judo. Although President Samaranch expressed a favorable opinion of women's judo, IOC members from the Eastern European countries such as the Soviet Union and Hungary opposed the adoption of women's judo as an Olympic sport. This conflict could be attributed to the context of the Cold War, when women's judo was developing to a greater extent in Western countries. In addition, Shigeyoshi Matsumae, the Japanese-born president who succeeded Palmer, has been described as having a favorable view of women's judo. However, the letters he sent to the IOC mostly expressed a desire for the continuation of the men's open category, indicating a strategic consideration of maintaining the open category alongside the adoption of women's judo as an Olympic sport.
Keywords: Διεθνής Ολυμπιακή Επιτροπή; Ολυμπιακά αθλήματα - Γυναίκες; Τζούντο; Τζούντο για γυναίκες - Ιστορία; Πολεμικές τέχνες; International Olympic Committee; Olympic games - Women; Judo; Judo for women - History; Martial arts; Judo; Women's Judo; Olympics; Women's Sports; IOC